Cross-Border Commercial Dynamics and Migratory Mobility in Far Southern Peru: A Literature Review on Social Networks and Identities, 1990-2020 - Villarroel Vargas, Josue Daniel (2025)
Migration in southern Peru is determined by a cross-border socioeconomic context that involves Peru, Chile, and Bolivia. This research analyzes academic literature on how southern Peruvian and foreign populations participate in migratory and commercial dynamics within regions characterized by their border condition. An analytical review of academic literature published between 2011-2023 on migratory processes occurring between 1990-2020 was conducted using platforms such as Google Scholar and Scielo. The analysis was structured around three thematic axes: configuration of cross-border migratory networks, articulation between commercial activities and population mobility, and identity construction processes of different migrant groups. The results show that cross-border commercial activity constitutes a persistent historical factor since colonial times, reconfigured after the War of the Pacific and transformed by Andean migrations since the mid-20th century and Venezuelan migrations in the 21st century. These dynamics have generated significant transformations in the commercial, demographic, and identity structure in cities such as Tacna and Arica, consolidating a cross-border space where commercial practices transcend geopolitical boundaries and articulate complex social networks.